Diethyldithiocarbamate complex with copper: the mechanism of action in cancer cells - Skrott, Zdenek; Cvek, Boris (Mini reviews in medicinal chemistry, 2012)
The idea of "repurposing" of existing drugs provides an effective way to develop and identify new therapies. Disulfiram (Antabuse), a drug commonly used for the treatment of alcoholism, shows promising anticancer activity in both preclinical and clinical studies. In the human body, disulfiram is rapidly converted to its reduced metabolite, diethyldithiocarbamate. If copper ions are available, a bis(diethyldithiocarbamate)-copper(II) complex is formed. Disulfiram's selective anticancer activity is attributed to the copper(II) complex's ability to inhibit the cellular proteasome. It is assumed that the complex inhibits the proteasome by a mechanism that is distinct to the clinically used drug bortezomib, targeting the 19S rather than the 20S proteasome. This difference could be explained by inhibition of the JAMM domain of the POH1 subunit within the lid of the 19S proteasome.
Keywords: Ditiocarb; nádorové buněčné linie; Breast Neoplasms; Coordination Complexes; Pyrazines; Copper; komplexní sloučeniny; kyseliny boronové; Bortezomib; Proteasome Endopeptidase Complex; Proteasome Inhibitors; měď; Oxidative Stress; Cell Line, Tumor; proteasomový endopeptidasový komplex; Antineoplastic Agents; protinádorové látky; bortezomib; Humans; inhibitory proteasomu; dithiokarb; nádory prsu; oxidační stres; pyraziny; Boronic Acids; lidé